Coronavirus pandemic and its effect on African religiosity - Mbosowo Bassey Udok; Clement Usen Eton; Ekpenyong Nyong Akpanika (International Journal of Humanities and Innovation (IJHI), 2020)
Coronavirus is the latest pandemic that is challenging all spheres of the human economy globally. The popular "lockdown", which is a means used to ameliorate this pandemic's devastating effect, was adopted by all the countries of the world mainly to soothe human health conditions while other sectors of the global economy were also punctured. The long-term preparation towards the year 2020 for "Vision 2020" otherwise, "sustainable development" was horrifically traumatized. Moreover, African religious culture expressed as God's sovereignty and communalism suffers a great deal. This work seeks to investigate the effect of the coronavirus pandemic on African religiosity. The paper adopts the historical/ descriptive method. It attempts to trace the present pandemic with previous ones and articulate the strength of African religiosity in the face of any pandemic situation. The finding shows that the sense of communalism has since been hijacked when political leaders think selfishly only of themselves at the community's standard members' detriments. The work concludes that the global pandemic has been not only a misfortune but also a blessing, God's sovereign over the universe may allow the pandemic so that as the whole world is coerced into quarantine or lockdown, the earth may have a natural management and rejuvenation.